Development and evaluation of fluid mechanics laboratory curriculum: a case study of the University of Ibadan, Nigeria (2004)
Mechanics in the University of Ibadan, Nigeria. The University has been equipped with standard laboratory for the Leaching of Fluid mechanics, but over the years some equipment have broken down and affected the leaching of Fluid Mechanics. All over the years the needs of the students have changed. This paper starts by reporting the rehabilitation and commissioning of one of the equipment. And then goes ahead to formulate the laboratory exercises required to be performed by the students in Fluid Mechanics before graduation in B.Sc degree programme bearing in mind the functionality of existing equipment and the environment awaiting the students on graduation. Several improvements have been made and documentation done. The paper concludes that in most first generation Universities in Nigeria, Fluid Mechanics laboratories are well equipped, but most of the equipment are not functioning because of minor elements that could have been improved and installed. It recommends that with little funding and commitment of staff and students this laboratory would be kept running to meet the need of Nigerian Engineering students.